KESEJAHTERAAN PSIKOLOGIS PADA MAHASISWA RANTAU UNIVERSITAS SAHID SURAKARTA (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Students who leave their home area to live for some time in another area are called overseas students. Becoming an overseas student is not an easy thing, apart from the dissatisfaction of a student, it often creates feelings of discomfort and unhappiness which results in poor psychological well-being for overseas students. This research was conducted with the aim of knowing the Psychological Well-being of Overseas Students at Sahid University, Surakarta. In this study using qualitative methods with observation and interview data collection techniques. The informants of this study were students from overseas outside Java who studied at Sahid University, Surakarta, totaling 7 informants. The results of this research are the psychological well-being of overseas students outside Java who study at Sahid University, Surakarta, in general 4 have good psychological well-being, 3 of them have poor psychological well-being, these 3 informants must be able to improve aspects of self-acceptance and aspects of development self.